Analysis of Factors Influencing Workplace Accidents against Workers at PT. Dok and Perkapalan Gandasari Indonesia In 2025 - Saribu Sinaga, B. Alvaro Buttu; Thamrin, Yahya; Wahyu, Atjo; Muis, Masyitha; Salam, Abdul (International Journal of Statistics in Medical Research, 2026)
The shipyard industry is recognized as a high-risk sector for occupational accidents due to the complex interaction between human factors, workplace conditions, and safety management systems; therefore, the increasing operational activities at PT. Dok and Perkapalan Gandasari Indonesia necessitate effective occupational safety management to minimize accident risks. This study aims to analyze the factors influencing occupational accidents among workers at PT. Dok and Perkapalan Gandasari Indonesia in 2025. The study using an analytic observational design with a cross-sectional approach, involving 191 workers selected through simple random sampling; data were collected using structured questionnaires and observation sheets, then analyzed using the Chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis. The results showed that unsafe acts, unsafe conditions, work fatigue, and training experience were significantly associated with occupational accidents (p < 0.05); moreover, multivariate analysis indicated that work fatigue was the most dominant risk factor (OR = 15.311), followed by unsafe acts as a significant predictor in the final model, while unsafe conditions and training experience were not statistically significant despite showing a tendency to increase risk. In conclusion, work fatigue is the most dominant factor contributing to occupational accidents, followed by unsafe acts. Therefore, prevention efforts should prioritize controlling work fatigue through adequate regulation of working hours and rest periods, alongside strengthening control of unsafe behaviors, improving workplace conditions, and enhancing continuous safety training programs.